The potential distribution prediction of the invasive alien species Acacia decurrens Wild., in Indonesia - Whisnu Febry Afrianto (Hasanuddin University, 2021)
Acacia deccurens Wild. has been reported as invasive alien species (IAS) in several areas of Indonesia. Climate change may impact IAS to be more invader. The study aimed was to develop a species distribution model of A. deccurens to depict the potential distribution under climate change in Indonesia. Biodiversity and Climate Change Virtual Laboratory (BCCVL) was used to examine a species distribution model (SDM) of A. decurrens in Indonesia based on climate variables and its naturalized distribution to predict the project distribution under current and future climate conditions. The data was collected from Global Biodiversity Information Facility (GBIF) to identify the species occurrences. The climate variables used in this study were temperature and precipitation layers based on WorldClim, current climate (1950-2000), 2.5 arcmin ( 5km). The SDM of the Generalized Linear Model (GLM) was utilized to predict the response variable as a function of multiple predictor variables. We selected four IPCC Representative Concentration Pathways (RCP) 2.6, 4.5, 6.0, and 8.5 for 2050. The prediction of the distribution of A. deccurens in 2050 showed that it was likely to decrease in Indonesia (mostly found only in Sumatra and Sulawesi Island). Almost all climate variables used in this study were responsive to A. decurrens distribution, except B09 - mean temperature of the driest quarter. The ROC plot showed excellent values (0.99). The information of the potential distribution on IAS under current and future climate scenarios can be used for policymakers and stakeholders to manage and handle the invasion.